A Social Parasite Evolved Reproductive Isolation from Its Fungus-Growing Ant Host in Sympatry - Rabeling, Christian; Schultz, Ted R.; Pierce, Naomi E.; Bacci, Maurício [UNESP] (Cell Press, 2014)
Inquiline social parasitic ant species exploit colonies of other ant species mainly by producing sexual offspring that are raised by the host. Ant social parasites and their hosts are often close relatives (Emery's rule), and two main hypotheses compete to explain the parasites' evolutionary origins: (1) the interspecific hypothesis proposes an allopatric speciation scenario for the parasite, whereas (2) the intraspecific hypothesis postulates that the parasite evolves directly from its host in sympatry [1-10]. Evidence in support of the intraspecific hypothesis has been accumulating for ants [3, 5, 7, 9-12], but sympatric speciation remains controversial as a general speciation mechanism for inquiline parasites. Here we use molecular phylogenetics to assess whether the socially parasitic fungus-growing ant Mycocepurus castrator speciated from its host Mycocepurus goeldii in sympatry. Based on differing patterns of relationship in mitochondrial and individual nuclear genes, we conclude that host and parasite occupy a temporal window in which lineage sorting has taken place in the mitochondrial genes but not yet in the nuclear alleles. We infer that the host originated first and that the parasite originated subsequently from a subset of the host species' populations, providing empirical support for the hypothesis that inquiline parasites can evolve reproductive isolation while living sympatrically with their hosts.